A comparison of the pathological, clinical and radiographical, features of cryptogenic organising pneumonia, acute fibrinous and organising pneumonia and granulomatous organising pneumonia. Issue 6 (5th March 2015) - Feinstein, Marc B; DeSouza, Shilpa A; Moreira, Andre L; Stover, Diane E; Heelan, Robert T; Iyriboz, Tunç A; Taur, Ying; Travis, William D
Abstract : Aims: Cryptogenic organising pneumonia (COP) and acute fibrinous and organising pneumonia (AFOP) are recognised patterns of organising pneumonia (OP), a condition that resembles pneumonia but is not caused by infection. We have recognised granulomatous organising pneumonia (GOP) to be a similar histopathological entity where non-necrotising granulomata are intimately associated with the organising connective tissue. To what degree COP, AFOP and GOP represent distinct clinical and pathological disorders is unknown. This cross-sectional study sought to compare the pathological, clinical, and radiographical features of these OP patterns. Methods: Surgical lung biopsy specimens were reviewed for consecutive patients referred with OP to a metropolitan cancer centre. Clinical information and CT images were acquired from the hospital electronic medical record to determine the clinical and CT characteristics of each OP pattern. Results: Sixty-one patients (35 men, 26 women), mean age 61.5 years (range 8–85 years), were available for analysis. Of these, 43 patients (70%) had at least one prior cancer; 27 (44%) had received chemotherapy and 18 (30%) had received radiation. Approximately, half (32 patients) had respiratory symptoms, most commonly cough, dyspnoea and/or wheezing. While symptoms and mortality rates were not different among OP groups, AFOP patients more commonly had fever (p=0.04). GOP patients less commonly had received chemotherapy (p=0.03) and were more likely to present as masses/nodules (p=0.04). Conclusions: AFOP and GOP, a newly described OP form, possess clinical and pathological findings that set it apart from a COP, suggesting an emerging spectrum of OP.